2019
DOI: 10.1111/bju.14883
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an optimal lymph node yield for penile squamous cell carcinoma: prognostic impact of surgical dissection

Abstract: Objective To evaluate the prognostic impact of lymph node yield (LNY) on survival outcomes for penile squamous cell carcinoma (SCC). Patients and methods In all, 532 patients who underwent inguinal LN dissection (ILND) across tertiary referral centres from Europe, China, Brazil and North America were retrospectively evaluated. From this cohort, 198 patients received pelvic LND (PLND).We identified threshold values for ILND and PLND using receiver operating characteristic curves. We tested prognostic value of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Our risk calculator established and validated the importance of three prognostic factors, namely pN 3 status, ILNM ratio and surgical margin status of the penile lesion. Although these factors have previously been found to be associated with an increased risk of cancer recurrence and adverse outcomes [18–21], we proved their independent correlation with recurrence, and developed an easy‐to‐use, readily accessible risk stratification tool. Moreover, the realisation of the risk calculator‐derived tertiles serves as a practical example of how the risk groups can be abstracted in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Our risk calculator established and validated the importance of three prognostic factors, namely pN 3 status, ILNM ratio and surgical margin status of the penile lesion. Although these factors have previously been found to be associated with an increased risk of cancer recurrence and adverse outcomes [18–21], we proved their independent correlation with recurrence, and developed an easy‐to‐use, readily accessible risk stratification tool. Moreover, the realisation of the risk calculator‐derived tertiles serves as a practical example of how the risk groups can be abstracted in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a lymph node yield of ≥9 was found to be a predictor for RFS after adjustment for baseline characteristics. Although a distinction of DSS, OS, and RFS differences in patients that underwent unilateral as opposed to bilateral PLND was not undertaken, this study established an LN threshold that may be more readily obtained with bilateral dissections and that may provide a benefit in patients harboring pelvic LNM [11].…”
Section: Pelvic Lymph Node Yield Impacts Survivalmentioning
confidence: 88%
“…Chipollini et al performed PLND in 198 chemonaïve patients, of which 106 (53.5%) were bilateral dissections. The median number of lymph nodes (LN) and the median number of positive LN were 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) and 2 (1-4), respectively. The survival analysis revealed that patients with a lymph node yield of ≥9 LN had better 5-year disease-specific survival (DSS) (64.2% vs. 47.2%), overall survival (OS) (60.3% vs. 39.8%), and recurrencefree survival (RFS) (60.3% vs. 43.2%).…”
Section: Pelvic Lymph Node Yield Impacts Survivalmentioning
confidence: 99%
“…Prognosis of patients harbouring pSCC is largely influenced by the initial stage of the disease, ranging from long survival in penile‐localised tumours treated by immediate surgery [1], to rapidly progressive disease in lymph node metastatic cases [2,3]. In this context, the identification of palpable groin lymph node metastases has been regarded as one of the most important predictors of poor overall survival (OS) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Using one of the largest multi‐institutional database of patients with pSCC [4,18,19], we aimed to identify the optimal candidates for NAC amongst cN+ patients. We focussed on patients with pSCC with palpable and/or imaging‐detected groin lymph node metastases, who underwent local excision and inguinal lymph node dissection (ILND).…”
Section: Introductionmentioning
confidence: 99%